KESALAHAN PENGGUNAAN BAHASA INDONESIA DALAM OPINI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA INDONESIA UNIVERSITAS TANJUNGPURA - Fauzanna, Sekar Harum; Sulissusiawan, Ahadi; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to describe Indonesian language usage errors in opinions written by students of the Indonesian Language Education Study Program at Tanjungpura University. The focus of the research includes three main aspects, namely spelling errors (use of letters and punctuation marks), diction (word selection), and the use of sentences based on effectiveness. The method used is descriptive with a qualitative approach. The data source comes from mass media Pontianak Post and Gencil News. The data in this study are in the form of Indonesian language usage errors related to spelling (use of letters and punctuation marks), diction (word selection), and the use of sentences based on effectiveness in opinions. The data collection technique was conducted indirectly through content analysis and documentation study. The results show that students still experience various errors in Indonesian language. Spelling errors include the use of capital letters, italics, comma punctuation marks, and hyphens. Diction errors are found in the aspect of accuracy and accuracy of word selection. Meanwhile, sentence usage errors are related to the effectiveness of sentence structure, especially in the use of incoherent subjects, predicates, and adverbs. This research contributes to efforts to improve students' language competence and their writing skills